Infrastructure and Enrolment of Scheduled Tribe Students in India - K, Damodaran (International Journal of Asian Education, 2023)
This paper examines the school infrastructure and student enrolment among the tribal community in India. Data from the UDISE+ Reports of the Government of India for 2012-13 to 2020-21 was used for the analysis. Tribal welfare schools in the country increased between 2012-13 and 2014-15 before declining. In tribal welfare schools, water access has improved, although many schools still lack drinking water and handwash facilities. One-fifth of tribal welfare schools do not have restrooms, which infers open defecation practices. Other facilities, such as the library, playground, electricity, and computers, are unavailable to all the tribal welfare schools. However, meager school improvements, enrolment, and infrastructure have been witnessed since 2019. Given this, it is critical to stress that an increasing number of schools with good infrastructure would encourage the tribal students' enrollment. Therefore, equity and high-quality education for all citizens can aid in a country's pursuit of sustainable growth.